The house with a dragon in it - Lake, Nick (Simon & Schuster Books for Young Readers, 2024)
When a mysterious hole opens up in her new foster family's living room, Summer encounters a dragon who offers her three wishes, but as she uses the wishes, the magic takes a dark turn and jeopardizes Summer's deepest desire for a home.